2009
DOI: 10.1590/s0066-782x2009000800009
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre variáveis de composição corporal e metabólica em adolescentes do sexo feminino

Abstract: SummaryBackground: Analysis of metabolic alterations and body composition in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
31

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 9 publications
2
9
0
31
Order By: Relevance
“…Changes in glucose metabolism, blood pressure, and lipid profile were also found by other studies on adolescents of the same age group [19][20] . Table 4.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Changes in glucose metabolism, blood pressure, and lipid profile were also found by other studies on adolescents of the same age group [19][20] . Table 4.…”
Section: Discussionsupporting
confidence: 78%
“…In population-based studies, blood pressure is related with the risk of death and disease 17 . Faria et al 20 found a 5.0% prevalence of high blood pressure in adolescents, and Pinto et al 31 found that 5.6% and 9.9% of the adolescents aged 10 to 14 years from Bahia, Brazil, were hypertensive and prehypertensive, respectively.…”
Section: Total Femalementioning
confidence: 99%
“…Resultado semelhante foi encontrado entre 100 meninas de 14 a 17 anos, com e sem SM, avaliadas em Viçosa, Minas Gerais [15].…”
Section: Discussionunclassified
“…Sabe-se que a adolescência é uma fase importante para adoção de hábitos saudáveis que podem garantir crescimento e desenvolvimento adequados e influenciar muitos aspectos da vida adulta [15]. Por isso, uma alimentação adequada durante esse período é crucial para uma vida saudável e para a prevenção, em longo prazo, de alterações metabólicas e doenças crônicas não transmissíveis [16].…”
Section: Introductionunclassified
“…Informações sobre a gordura corporal são importantes para a avaliação e controle do peso corporal, tornando-se ainda mais necessárias quando se fala de saúde e de crianças e adolescentes (3). A identificação do excesso de peso corporal e a determinação da distribuição dos componentes corporais em crianças, de maneira correta e precoce, pode auxiliar no desenvolvimento de mecanismos para a prevenção e o tratamento deste importante fator de risco, a obesidade (4).…”
Section: Introductionunclassified